IMPLEMENTASI KEBIJAKAN KOTA LAYAK ANAK (KLA) DI KABUPATEN KAMPAR - Aulio Bisma Parneto; Harapan Tua Ricky Freddy Simanjuntak (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Child-friendly cities (KLA) are districts/cities that have a child rights-based development system through the integration of government, community and business commitments and resources, which are planned in a comprehensive and sustainable manner in policies, programs and activities to ensure the rights and protection of children in the future. front . There are still many children whose civil rights have not been fulfilled, the lack of facilities and infrastructure to reach a child-friendly city. As well as the lack of an active role from several implementers. To Realize a Child Friendly City (KLA) Kampar Regency through the PPKBP3A Office has made several programs/activities related to child-friendly city-based development (KLA) in 2020. These programs/activities are based on policies that have been issued by the central government and are based on 5 points of fulfillment child. This study examines how the implementation of child-friendly city development in Kampar Regency. This research is descriptive using qualitative methods. Informants selected using purposive sampling method. The result of the research that the researcher got is that the implementation of Child Friendly City development policies in Kampar Regency has not run fully optimally. This is due to the involvement of all sectors, both the government, private and community sectors in this policy, so that the Convention on the Rights of the Child (CRC) is slow. So that it has an impact on the understanding of Child Friendly Cities and the lack of skills and capacity of the regional apparatus who carry out this policy.